The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11665-009-9551-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Speeds, Materials, and Tool Rake Angles on Metallic Particle Emission During Orthogonal Cutting

Abstract: Dry high speed machining has been proposed as a viable and cost-effective process in metal cutting industries. However, it produces fine and ultra-fine metallic particles, also referred to as dust, which can be harmful to the machine-tool operator. The risk associated with exposure to metallic particles increases as the particle size decreases. For machining processes, little data exist on the size and distribution of dust generated during the shaping of materials. In order to reduce or eliminate the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Experimental studies have shown that dry aerosols generated during metal machining depend on the workpiece material and its conditions, as well as on the cutting parameters (Ref 21,28,29) and the tool geometry (Ref 30,31) used.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental studies have shown that dry aerosols generated during metal machining depend on the workpiece material and its conditions, as well as on the cutting parameters (Ref 21,28,29) and the tool geometry (Ref 30,31) used.…”
Section: Introductionmentioning
confidence: 99%
“…To the authorsÕ knowledge, the literature contains only limited models for predicting particle emissions during machining processes (Ref 27,30,31). Zipf and Bieniawski (Ref 32) proposed a phenomenological interpretation for fine particle emission, but only during coal machining, thus making it inapplicable to metals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations